Magnetic resonance enterography/enteroclysis in acquired small bowel diverticulitis and small bowel diverticulosis - Mansoori, Bahar; Delaney, Conor P.; Willis, Joseph E.; Paspulati, Raj M.; Ros, Pablo R.; Schmid-Tannwald, Christine; Herrmann, Karin A. (European radiology, 2016)
Purpose Small bowel (SB) diverticulosis is a rare disorder that may entail serious complications, including SB diverticulitis. Both are often missed in imaging. Magnetic resonance enterography/enteroclysis (MRE) is increasingly used to assess SB disease; awareness of the appearance of SB diverticulitis is essential to ensure appropriate management. Our aim was to systematically describe imaging characteristics of SB diverticulosis and diverticulitis in MRE. Methods This retrospective, HIPAA-compliant study identified 186 patients with suspected SB diverticulosis/diverticulitis in medical databases of two tertiary medical centres between 2005 and 2011. Patients with surgically confirmed diagnoses of SB diverticulosis/diverticulitis were included. Two observers analyzed MR images for the presence, location, number, and size of diverticula, wall thickness, and mural and extramural patterns of inflammation. Results Seven patients were recruited. MRI analysis showed multiple diverticula in all (100 %). Diverticular size ranged from 0.5 to 6 cm. Prevalence of diverticula was higher in the proximal than the distal SB (jejunum 86 %, ileum 57 %, distal ileum43%). Diverticulitis occurred in 3/7 patients (43 %) showing asymmetric bowel wall thickening and focal mesenteric inflammation. Conclusion SB diverticulitis demonstrates characteristic MRE imaging features to distinguish this rare disorder from more common diseases. Asymmetric, focal mesenteric and mural inflammation and presence of multiple diverticula are keys to diagnosis. Key points • Small bowel diverticulosis and diverticulitis is rare and often missed in imaging • Acquired small bowel diverticula are variable in size and number • Small bowel diverticulitis demonstrates characteristic features on MR enterography/enteroclysis • A focal or segmental asymmetric small bowel inflammation should prompt the search for diverticula